Tracking the Burden of Type 2 Diabetes Mellitus Among Libyan Patients in Three Populated Districts of Tripoli, Libya (Razi Medical Journal, 2025)
The rising global incidence of Type 2 Diabetes Mellitus (T2DM) is a major contributor to increased morbidity and mortality. Research consistently links type 2 diabetes mellitus (T2DM) with various hematological and lipid abnormalities. However, studies in Libya that examine the relationship between these factors in T2DM patients and correlate them with geographical distribution are scarce. This study aims to evaluate the variations in hematological and lipid profiles among Libyan individuals with type 2 diabetes mellitus (T2DM) and to investigate potential correlations between these parameters. Additionally, it seeks to conduct T2DM surveillance in densely populated regions. A cross-sectional study was conducted at laboratories located in three different districts of Tripoli: Ghout Al Shaal Specialized Hospital, Abu Salim Hospital, and Al Sarai Laboratory in Hay Al Andalus. A total of 261 Libyan participants were divided into 170 patients with type 2 diabetes and 91 non-diabetic (controls), aged 50-85 years. Anthropometric data (weight, height, and body mass index (BMI)) were measured using standard protocols. Complete blood count (CBC) and lipid profile analysis were measured using the Sysmex XP-300 automated hematology analyzer and the Roche Cobas Integra 400 Plus system, respectively. Data were analyzed statistically using GraphPad Prism and SPSS version 27. A p-value of
Keywords: Lipid Profile, Haematological Parameters, Type 2 Diabetes Mellitus, Dyslipidemia, Districts.